The master dashboard screen on a highly-technical computer: The metaphorical portrayal of the IMMUNE SYSTEM in English and Serbian popular medical discourse - Nadežda Silaški (Ibérica)
Due to the increased interest in immunity and the immune system, mostly triggered by the recent Covid-19 pandemic, there has been a proliferation of online texts dealing with these concepts in an easily accessible manner. In this paper we compare the metaphorical portrayals of the IMMUNE SYSTEM in 84 English and Serbian online magazine articles and blog posts, mostly published in the period 2020-2023, and investigate how such metaphorical representations facilitate the explanation of this abstract concept to non-experts and respond to new communicative contexts. Specifically, our research aims are: 1) to identify the source domains employed in English and Serbian online popular medicine texts to conceptualize the various aspects of the IMMUNE SYSTEM; 2) to investigate the similarities and differences between the two languages in the source domains and metaphors used to popularize the knowledge about the IMMUNE SYSTEM. The findings reveal considerable overlap between English and Serbian both on conceptual and linguistic planes and in the use of metaphor in linking different audiences and discourses, while popular medicine texts in English show a greater richness in metaphor and exhibit a more vivid metaphoric imagery belonging to distinct source domains. Our paper contributes to contrastive explorations of the role of metaphor in the popularization of knowledge in the specific field of medical science.